Effects of Turmeric, Cinnamon, and Lemon Extracts on Shelf Life, Nutrients, and Preservation of Carp Fish in Cold Storage - Samira Maleki Mugahi; Ali Aberoumand; Saeed Ziaei-nejad (Journal of Food Quality)
The present study aimed to investigate the effect of extracts of turmeric, cinnamon, and lemon on shelf life, macronutrients, and oxidative spoilage of the carp fish in cold storage at 4°C. Fishes were divided into five groups: control (NT); immersed fish in extracts of cinnamon, turmeric, and lemon (CTL); immersed fish in extracts of lemon and turmeric (LT); immersed fish in extracts of cinnamon and turmeric (CT); and immersed fish in extracts of lemon and cinnamon (LC). Results showed immersion of the carp fillet in extracts of turmeric, cinnamon, and lemon improved spoilage indices such as thiobarbituric acid, volatile nitrogen bases, and pH. The used extracts maintained the nutritional value and increased the fish’s shelf life. The compounds existed in the studied extracts decreased the values of the spoilage indices during cold storage. The highest spoilage indices were found for CL and CT treatments, and the lowest was for CTL treatment. The total bacterial load as well as the number of psychrophilic bacteria in the fish fillet found a significant decrease compared to the NT. Therefore, the best treatment was CTL, and inappropriate treatments were CT and CL. The fish shelf life for nine days was extended with the used extracts because the total count of cryophilic bacteria was 0.41 × 104 ± 0.50, which was the lowest compared to other treatments.